Targeted Exome Sequencing of Genes Involved in Rare CNVs in Early-Onset Severe Obesity - Loid, Petra; Pekkinen, Minna; Mustila, Taina; Tossavainen, Päivi; Viljakainen, Heli; Lindstrand, Anna; Mäkitie, Outi (Frontiers in Genetics, 2022)
Context: Rare copy number variants (CNVs) have been associated with the development of severe obesity. However, the potential disease-causing contribution of individual genes within the region of CNVs is often not known. Objective: Screening of rare variants in genes involved in CNVs in Finnish patients with severe early-onset obesity to find candidate genes linked to severe obesity. Methods: Custom-made targeted exome sequencing panel to search for rare (minor allele frequency < 0.1%) variants in genes affected by previously identified CNVs in 92 subjects (median age 14 years) with early-onset severe obesity (median body mass index (BMI) Z-score + 4.0). Results: We identified thirteen rare heterozygous variants of unknown significance in eleven study subjects in twelve of the CNV genes. Two rare missense variants (p.Pro405Arg and p.Tyr232Cys) were found in SORCS1, a gene highly expressed in the brain and previously linked to diabetes risk. Four rare variants were in genes in the proximal 16p11.2 region (a frameshift variant in TAOK2 and missense variants in SEZ6L2, ALDOA and KIF22) and three rare missense variants were in genes in the 22q11.21 region (AIFM3, ARVCF and KLHL22). Conclusions: We report several rare variants in CNV genes in patients with childhood obesity. However, the role of the individual genes in the previously identified rare CNVs to development of obesity remains uncertain. More studies are needed to understand the potential role of the specific genes within obesity associated CNVs.